2004
DOI: 10.1128/jcm.42.7.2884-2889.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Severe Acute Respiratory Syndrome (SARS) Coronavirus Nucleocapsid Protein in SARS Patients by Enzyme-Linked Immunosorbent Assay

Abstract: We report the development of an enzyme-linked immunosorbent assay (ELISA) for the detection of severe acute respiratory syndrome (SARS) coronavirus (CoV) nucleocapsid protein. The assay was carried out with hyperimmune polyclonal nucleocapsid-specific antibodies from guinea pigs and rabbits immunized with recombinant His 6 -tagged SARS CoV nucleocapsid protein. The assay was used for the detection of SARS CoV nucleocapsid protein in nasopharyngeal aspirate, urine, and fecal samples collected from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 13 publications
3
129
0
4
Order By: Relevance
“…In a separate study, Lau et al (2004) An analysis of the spread of SARS in Hong Kong showed that the epidemic had a period of exponential growth followed by a time of stability leading to decay thereafter Riley et al, 2003). Most patients had symptoms within 14 days of infection (range 6.3-16.7 days).…”
Section: Epidemiology Of Sarsmentioning
confidence: 97%
“…In a separate study, Lau et al (2004) An analysis of the spread of SARS in Hong Kong showed that the epidemic had a period of exponential growth followed by a time of stability leading to decay thereafter Riley et al, 2003). Most patients had symptoms within 14 days of infection (range 6.3-16.7 days).…”
Section: Epidemiology Of Sarsmentioning
confidence: 97%
“…The assay is designed to detect the most abundant and conserved viral antigen nucleocapsid protein NP (Di et al 2005;Hiscox et al 1995;Lau et al 2004;Rota et al 2003;Suresh et al 2008) because its presence in different body fluids (serum, urine, nasopharyngeal aspirate, throat wash samples, and saliva) is suggestive of current infection. Three different monoclonal antibodies that recognize different epitopes on NP antigen and the anti-HRPO monoclonal antibody were employed to generate the BsMAb using hybrid-hybridoma technology.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…noroviruses), illustrate that, should a novel pathogen with efficient foodborne transmission arise, we are likely to be ill prepared to handle such an event. SARS coronavirus was spread into the human population through the preparation and consumption of food of animal origin, which appears to have contracted the infection from another reservoir, probably bats (Lau et al, 2004b). Infectious H5N1 avian influenza virus has been cultured from duck meat, and the consumption of duck blood has resulted in the infection of humans (Tumpey et al, 2003 reviewed the food safety aspects of avian influenza and of novel influenza virus H1N1, concluding that foodborne infection with avian influenza is unlikely but can not be ruled out entirely, and that food contaminated with nH1N1 influenza viruses does not appear to be a vehicle for infection in humans.…”
Section: Viruses Occasionally Reported As Foodbornementioning
confidence: 99%